Development of Interactive Learning Media Based on Genially in Informatics Subjects to Improve Digital Literacy of SMPN 4 Madapangga Students - Ifrianingsih, Ifrianingsih; Syarifudin, Syarifudin; Fitrianingsih, Nur (FKIP - Universitas Riau, 2025)
The rapid development of digital technology demands innovation in the learning process to make it more interactive and relevant to 21st-century educational needs. However, Informatics learning at SMPN 4 Madapangga is still dominated by conventional and static media, resulting in low student engagement and digital literacy skills. Based on these conditions, this study aims to develop interactive learning media based on Genially in the Informatics subject for eighth-grade students to improve their digital literacy. The research employed the Research and Development (R&D) method using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The validation results showed that the media obtained feasibility scores of 83%, 89%, and 95% from two media experts and one material expert, respectively, categorized as very feasible. The practicality test involving 20 students yielded a score of 93.88% (very practical), while the digital literacy assessment reached 94.76% (very good). The effectiveness test using the N-Gain calculation produced an average score of 0.56 (moderate category), indicating that the media is quite effective in improving learning outcomes. Therefore, Genially-based learning media are declared feasible, practical, and effective for enhancing students’ digital literacy and supporting the implementation of the student-centered and technology-integrated Merdeka Curriculum.